HUMAN RESOURCE ASPECTS IN MARKETING EDUCATIONAL SERVICES - Eko Satria Wahyu Utama; Fikrial Nurfaizin; Jaja Abdul Jabar; Anis Zohriah; Abdul Muin (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the role of human resources (HR) in marketing educational services, with a focus on the competence, motivation, and professionalism of educators and administrative staff. The research method used is descriptive qualitative research with data collection techniques through in-depth interviews, participant observation, and documentation studies at several educational institutions. The formulation of the research problem includes: (1) how HR competency influences the effectiveness of marketing educational services, (2) the influence of HR motivation and job satisfaction on service quality, and (3) the role of HR integration in educational marketing strategies. The results of the study indicate that HR has a strategic role in shaping the image and quality of educational services; HR competency and training improve marketing and service capabilities; HR satisfaction and motivation influence the quality of interactions with students and parents; and HR integration in marketing strategies is a key factor in the success of institutional promotion and branding. In conclusion, the success of marketing educational services is highly dependent on HR management and development, so educational institutions need to pay special attention to improving the quality, competence, and professionalism of HR to support competitiveness and customer satisfaction.